Cerebral Venous Sinus Thrombosis as a Rare Complication of Systemic Lupus Erythematosus: Subgroup Analysis of the VENOST Study - MİDİ, İPEK (ELSEVIER, 2019)
Aim: Systemic lupus erythematosus (SLE) is an unusual risk factor for cerebral venous sinus thrombosis (CVST). As few CVST patients with SLE have been reported, little is known regarding its frequency as an underlying etiology, clinical characteristics, or long-term outcome. We evaluated a large cohort of CVST patients with SLE in a multicenter study of cerebral venous thrombosis, the VENOST study, and their clinical characteristics. Material and Method: Among the 1144 CVST patients in the VENOST cohort, patients diagnosed with SLE were studied. Their demographic and clinical characteristics, etiological risk factors, venous involvement status, and outcomes were recorded. Results: In total, 15 (1.31%) of 1144 CVST patients had SLE. The mean age of these patients was 39.9 +/- 12.1 years and 13 (86.7%) were female. Presenting symptoms included headache (73.3%), visual field defects (40.0%), and altered consciousness (26.7%). The main sinuses involved were the transverse (60.0%), sagittal (40.0%), and sigmoid (20.0%) sinuses. Parenchymal involvement was not seen in 73.3% of the patients. On the modified Rankin scale, 92.9% of the patients scored 0-1 at the 1-month follow-up and 90.9% scored 0-1 at the 1-year follow-up. Conclusions: SLE was found in 1.31% of the CVST patients, most frequently in young women. Headache was the most common symptom and the CVST onset was chronic in the majority of cases. The patient outcomes were favorable. CVST should be suspected in SLE patients, even in those with isolated chronic headache symptoms with or without other neurological findings.
Keywords: Systemic lupus erythematosus; cerebral venous sinus thrombosis; headache; neurological symptoms; RISK-FACTORS; MANIFESTATIONS; MULTICENTER; PROGNOSIS; PATIENT; VEIN